Mixed Method for Holistic Insights in Human Resource Management Research - Taufik, Nuryanti; Rahayuningrat, Prahita Sri (Sharia Business Management UIN Raden Intan Lampung, 2025)
The development of research paradigms in economics and business has shifted from traditional positivist approaches to interpretive, constructivist, and critical perspectives. These paradigms allow for broader and more contextual exploration but often face data collection and integration limitations. Mixed methods have subsequently emerged as a research strategy that combines the strengths of quantitative and qualitative approaches to achieve a more comprehensive understanding. This article explores the significance of employing mixed methods in research within economics and business, particularly in human resource management (HRM). Integrating objective numerical data with in-depth qualitative insights in mixed methods is regarded as a solution to the limitations of traditional paradigms, offering enhanced validity through data triangulation. Examples of implementation across various HRM contexts from the restaurant industry in Korea to studies on knowledge-sharing behavior in Portugal illustrate how mixed methods contribute to richer insights into structural and human factors within organizations.